SMOKED FISH PROCESSING (KAHOLEO) IN ECONOMIC ASPECTS AND THE DEVELOPMENT SRATEGY OF COASTAL COMMUNITIES BONEATIRO VILLAGE, BUTON DISTRICT - Ismail Failu Mail; LM. Junaidin Sirza; Wa Ode Cahyani; Nila Nikmatia Bugis (Jurnal Pengabdian Pada Masyarakat MEMBANGUN NEGERI, 2020)
Field activities for management of aquatic or maritime resources are expected to build a new picture in the fisheries sector, especially for the younger generation, that fisheries are not inferior to other fields, can be an interesting, prospective, and respectable skill. Provide an explanation of the importance of the use of marine products in Boneatiro Village. The objectives of Community Service (CS) are: (1) Increase fishermen's knowledge about anchovy processing by smoking; (2) Increase fishermen's knowledge about anchovy smoking, so as to reduce the possibility of using preservatives such as formaldehyde and borax; (3) Providing information on how to do promotions about smoked anchovy that are attractive to customers; (4) Opening up business opportunities for community fishermen, especially Boneatiro Village, thereby increasing the economic income of the community. The CS location was carried out in Boneatiro Village, Kapuntori District, Buton Regency. CS was held from November to December 2019. The framework for solving the problems studied in this community service activity is by using two approaches, namely the extension and training approach. Coaching and evaluation activities are carried out to determine the effectiveness of the implementation of community service programs. The high potential of fisheries resources, especially the capture fisheries section of the Boneatiro Village fishermen community, requires a touch of technology so that the products obtained are not only sold in the form of fresh fish, but efforts can be made that can increase added value by processing smoked fish developed with liquid smoke technology. Apart from being a choice of products that can help the business sources of income for the fishing community of Boneatiro Village, the activity is expected to also increase the selling value of Boneatiro Village which is expected to become one of the promising marine tourism destinations.